MRI‐Visual Order–Disorder Micellar Nanostructures for Smart Cancer Theranostics. Issue 4 (25th August 2013) - Patra, Hirak K.; Khaliq, Nisar Ul; Romu, Thobias; Wiechec, Emilia; Borga, Magnus; Turner, Anthony P. F.; Tiwari, Ashutosh
<x xml:space="preserve">Abstract</x> The development of MRI‐visual order–disorder structures for cancer nanomedicine explores a pH‐triggered mechanism for theragnosis of tumor hallmark functions. Superparamagnetic iron oxide nanoparticles (SPIONs) stabilized with amphiphilic poly(styrene)‐b‐poly(acrylic acid)‐doxorubicin with folic acid (FA) surfacing are employed as a multi‐functional approach to specifically target, diagnose, and deliver drugs via a single nanoscopic platform for cancer therapy. The functional aspects of the micellar nanocomposite is investigated in vitro using human breast SkBr3 and colon cancer HCT116 cell lines for the delivery, release, localization, and anticancer activity of the drug. For the first time, concentration‐dependent T2‐weighted MRI contrast for a monolayer of clustered cancer cells is shown. The pH tunable order–disorder transition of the core–shell structure induces the relative changes in MRI contrast. The outcomes elucidate the potential of this material for smart cancer theranostics by delivering non‐invasive real‐time diagnosis, targeted therapy, and monitoring the course and response of the action before, during, and after the treatment regimen.